2000
DOI: 10.1093/emboj/19.21.5672
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl methylation of the phosphoprotein phosphatase 2A catalytic subunit promotes its functional association with regulatory subunits in vivo

Abstract: The phosphoprotein phosphatase 2A (PP2A) catalytic subunit contains a methyl ester on its C-terminus, which in mammalian cells is added by a speci®c carboxyl methyltransferase and removed by a speci®c carboxyl methylesterase. We have identi®ed genes in yeast that show signi®cant homology to human carboxyl methyltransferase and methylesterase. Extracts of wild-type yeast cells contain carboxyl methyltransferase activity, while extracts of strains deleted for one of the methyltransferase genes, PPM1, lack all ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
177
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 54 publications
15
177
1
Order By: Relevance
“…Within the B-type subunit pool, Rts1p (ROX three suppressor 1; the yeast homolog of PR61/B 0 ), is 12Â as abundant as Cdc55p (cell-division-cycle mutant 55; the yeast homolog of PR55/B), indicating that, at any given time, there will always be a free pool of Rts1p and that an as yet undefined mechanism must operate to permit competition between Cdc55p and Rts1p for binding to PP2A D . The same study also confirmed earlier reports demonstrating that, in yeast, subunit stability is not linked to heterotrimer formation [20][21][22][23][24]. However, in Drosophila melanogaster Schneider cells, the absence of all B-type subunits promotes the degradation of the A and C subunits, and vice versa [25,26], which indicates that PP2A enzymes are obligate trimers in this system.…”
Section: Pp2a a Structural Centipede With Multiple Functionssupporting
confidence: 91%
See 2 more Smart Citations
“…Within the B-type subunit pool, Rts1p (ROX three suppressor 1; the yeast homolog of PR61/B 0 ), is 12Â as abundant as Cdc55p (cell-division-cycle mutant 55; the yeast homolog of PR55/B), indicating that, at any given time, there will always be a free pool of Rts1p and that an as yet undefined mechanism must operate to permit competition between Cdc55p and Rts1p for binding to PP2A D . The same study also confirmed earlier reports demonstrating that, in yeast, subunit stability is not linked to heterotrimer formation [20][21][22][23][24]. However, in Drosophila melanogaster Schneider cells, the absence of all B-type subunits promotes the degradation of the A and C subunits, and vice versa [25,26], which indicates that PP2A enzymes are obligate trimers in this system.…”
Section: Pp2a a Structural Centipede With Multiple Functionssupporting
confidence: 91%
“…However, a variety of experimental approaches both in yeast and mammalian cells demonstrate that PP2A C methylation has a crucial role in B-type-subunit binding, specifically in the recruitment of PR55/B subunits [20][21][22][23]44,[51][52][53][54][55]. By contrast, the recruitment of A [44,[51][52][53]55], PR61/B 0 [21][22][23]55], PR72/B 00 [54,55] and striatin [44] does not strictly require PP2A C methylation in vivo, and binding of polyoma middle T [44,51] and a4 [20,56] is increased in the absence of methylation. In yeast, the deletion of PPM1 (protein phosphatase methyltransferase 1, which encodes the yeast LCMT1 ortholog) or the expression of PP2A C harboring a Leu309!Ala substitution, inhibits Cdc55p binding [20][21][22][23], whereas Tpd3p (tRNA-processing-deficient mutant 3; the yeast A subunit homolog) and Rts1p binding is only slightly diminished [20][21][22][23].…”
Section: Trends In Biochemical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the main dephosphorylating enzyme of α ‐synuclein is the B55 α containing heterotrimeric isoform of PP2A,13 and methylation of the C subunit of PP2A enhances the incorporation of the regulatory B55 α subunit into the catalytically active holoenzyme,3, 4, 5 the markedly decreased expression of the methylating enzyme LCMT‐1 in these conditions, and increased expression of the demethylating enzyme PME‐1, lead to a striking decrease in the methylated form of PP2A. These dysregulatory changes are not only particularly prominent in the substantia nigra pars compacta but also present in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In neuronal cells, most of the C subunit is associated with a conserved scaffold‐like A subunit, and one of several different regulatory B subunits that confer different substrate specificities on the resulting trimeric holoenzymes. The binding of different B subunits to the AC dimer is regulated by reversible carboxyl methylation of the C subunit 3, 4, 5. Thus, PP2A methylation is critical for its selective phosphatase activity toward different phospho‐protein substrates.…”
Section: Introductionmentioning
confidence: 99%